Integration of transcriptomics, proteomics, and metabolomics data for the detection of the human pathogenic Prototheca wickerhamii from a One Health perspective - Guo, Jian; Chen, Juan; Li, Teng; Gao, Lei; Jiang, Cizhong; Wu, Wenjuan (Frontiers in Cellular and Infection Microbiology, 2023)
Prototheca species are the only microalgae known to cause opportunistic infections in vertebrates and humans. Most cases of protothecosis in humans are caused by Prototheca wickerhamii, but knowledge of the pathogenicity and biology of Prototheca is limited. Globally, the diagnostic rate of Prototheca species infection is much lower than the actual rate of P. wickerhamii. The precise mechanisms underlying the pathogenesis of Prototheca infections remains unclear. In this study, we identified a strain of P. wickerhamii with atypical colony morphology. To reveal the morphological differences between P. wickerhamii S1 (mucous) and the molecular basis of its pathogenicity, the transcriptomics, proteomics, and metabolomics of two pathogenic P. wickerhamii strains and one environmental strain were analysed. Interestingly, mannan endo-1,4-β-mannosidase was significantly downregulated in P. wickerhamii S1, which contributes to a thinner cell wall in S1 compared to strains with typical colony morphology, and the toxicity of macrophages is reduced. Metabolite analysis revealed that the mucoid appearance of P. wickerhamii S1 may have been caused by an increase in linoleic acid, glycerol, and other metabolites. There still exists the to better understand the ecology, aetiology, and pathogenesis of P. wickerhamii, especially the transmission between humans, animals, and the environment, from a One Health perspective.